Microcystin-Leucine Arginine Causes Cytotoxic Effects in Sertoli Cells Resulting in Reproductive Dysfunction in Male Mice - Chen, Yabing (Sci Rep, 2016)
Microcystin-leucine arginine (MC-LR) is a potent toxin for Sertoli cells. However, the specific molecular mechanisms of MC-induced cytotoxicity still remain unclear. In this study, we performed a comprehensive analyses of changes of miRNAs and mRNAs in Sertoli cells treated with MC-LR. Through computational approaches, we showed the pivotal roles of differentially expressed miRNAs that were associated with cell metabolism, cellular growth and proliferation, cell-to-cell signaling and interaction and cellular movement. Ingenuity Pathway Analyses (IPA) revealed some differentially expressed miRNAs and mRNAs that may cause reproductive system diseases. Target gene analyses suggested that destruction in tight junctions (TJ) and adherens junctions (AJ) in testes may be mediated by miRNAs. Consistent with a significant enrichment of chemokine signaling pathways, we observed numerous macrophages in the testes of mice following treatment with MC-LR, which may cause testicular inflammation. Moreover, miR-98-5p and miR-758 were predicted to bind the 3′-UTR region of the mitogen-activated protein kinase 11 (MAPK11, p38 β isoform) gene which stimulates tumor necrosis factor-α (TNF-α) expression in Sertoli cells. TNF-α could interact with the tumor necrosis factor receptor 1 (TNFR1) on germ cells leading to induction of germ cell apoptosis. Collectively, our integrated miRNA/mRNA analyses provided a molecular paradigm, which was experimentally validated, for understanding MC-LR-induced cytotoxicity.